ANALISIS PENGELOLAAN DANA DESA GUNA KESEJAHTERAAN MASYARAKAT PADA DESA SEMOWO KECAMATAN PABELAN KABUPATEN SEMARANG - Wiwik Lestari; Dyah Palupiningtyas; Dyan Triana Putra; Septa Intiar; Umar Abdul Jabbar (Lembaga Pengembangan Kinerja Dosen, 2022)
This study identified 1) the obstacles faced in managing village funds for community welfare in Semowo Village, Pabelan District, Semarang Regency. 2) Management of village funds for community welfare in Semowo Village, Pabelan District, Semarang Regency. This research method is descriptive with a qualitative approach. The sources for this research consisted of 5 village officials in the Semowo Village area, Pabelan District, as well as village government officials. Data collection techniques used in the form of interviews, observation, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study indicate that program accountability is a part that is very much needed to measure the achievement of goals or results achieved by the government regarding the implementation of Village funds, besides that whether the government has other alternative programs that can provide maximum results and minimal costs.